Diving Into Emotions: An Illocutionary Acts Approach to Demi Lovato's "Heart Attack" Song Lyrics - Intan Ayu Destiani; Mohammad Ikhwan Rosyidi (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
Language conveys not only explicit meaning but also speakers' underlying intentions, which are examined in pragmatics through speech act theory, particularly the concept of illocutionary acts. This study investigates the types of illocutionary acts in Demi Lovato's Heart Attack, a contemporary English pop song that has received little attention from a pragmatic perspective despite extensive research on speech acts in song lyrics. It also explains how these acts interact to construct the song's central theme of fear of emotional vulnerability, providing a contextual interpretation beyond the classification of speech act types. This study employed a descriptive qualitative approach based on Searle's speech act theory. 25 utterances were identified and classified into four types of illocutionary acts: expressive (60%), assertive (24%), commissive (12%), and directive (4%), while no declarative acts were found. The predominance of expressive acts reflects the song's recurring emotions of fear, insecurity, and emotional restraint. These findings contribute to pragmatic research by demonstrating how illocutionary acts collectively shape meaning and emotional expression in contemporary popular music, extending existing scholarship on speech acts in song lyrics.